Genetic Analyses on Transgender Individuals: Impact on Physician Attitudes and Surgical Decision‐Making - Duygu Onur Cura; Ayfer Ülgenalp; Tufan Çankaya (Brain and Behavior)
ABSTRACT Purpose Genetic studies on the transgender and gender diverse (TGD) community have started to appear in the literature. However, there are limited studies on how genetic data will impact attitudes and perspectives toward TGD individuals. In this study, we investigated the impact of genetic alterations on physicians' attitudes toward TGD individuals and on physicians' decisions concerning gender confirmation surgery (GCS). In this context, we intended to highlight a number of strategies to reduce the inequalities that the TGD community is exposed to in accessing health‐care services. Method An online survey including the Turkish version of the Attitudes Toward Transgendered Individuals Scale (ATTIS) was completed by 224 physicians from relevant specialties. Scheffé and least significant difference (LSD) post hoc analysis methods were used to determine physicians' perspectives on whether genetic findings would cause TGD individuals to feel validated/invalidated. Multivariate multinomial logistic regression analysis was employed to assess their responses concerning the decision to perform GCS when genetic alterations had been identified. Results More than half of the physicians expressed the view that genetic analyses for TGD individuals would confer benefits (67.1%). Those who thought that the presence of gender–diversity‐related genetic alterations would have a “positive impact” on their GCS‐related decision to operate were found to have less positive attitudes toward TGD individuals (Bonferroni corrected p < 0.001). Multivariate multinomial logistic regression analysis revealed that age, presenting the odds ratio as the strongest factor, distinguished the “no impact” group from the reference “positive impact” group, particularly among those aged ≤ 35 years (3.299, 95% CI: 1.355–8.033; p = 0.009). Conclusion Although genetic analysis of TGD individuals is predicted to have a positive effect on physicians' attitudes toward them and on the GCS decision‐making process, it should be emphasized that the benefits for TGD individuals must outweigh the potential harm. The results showed that physicians need “early and continuing education” to develop a comprehensive perspective on gender identity. The most appropriate approach for genetic testing would be to include the TGD community in decision‐making processes and to develop guidelines for the interpretation of genetic data.